Disamenity effects of displaced villagers' resettlement community on housing price in China and implication for socio-spatial segregation. (May 2022) - Zhang, Mengzhu; Qiao, Si; Yeh, Anthony Gar-On
Abstract: In the 2010s, the return of the state in land expropriation and urban (re)development processes has resulted in a new type of neighborhood in urban China, namely, displaced villagers' resettlement community (DVRC). The government aimed to promote the social integration of land-lost peasants into urban society by placing DVRCs in areas with good accessibility and mixed land-use development. However, some studies found that the territorial stigmatization of DVRCs as poor and uncivilized neighborhoods has caused the depreciation of houses in DVRCs. Does this disamenity effect spill over to nearby houses? If yes, does this disamenity effect vary across space? This research uses Chengdu, the largest city in Western China, as the case study. A big data approach is used to analyze the list price of 53, 969 houses and their housing attributes. An ordinary least squares hedonic model is used to determine the effect of the proximity to DVRC on house price at an overall statistical level. Then, a mixed geographically weighted regression model is used to examine the spatial heterogeneity of this disamenity effect. The empirical results support the account that DVRCs depreciate nearby houses. In these underdeveloped suburban areas, the proximity to DVRCs is positively associated with housing prices because of its function as a proxy for the prospective proximity to urban service facilities. These findings indicate that the government trial of social integration promotion is not that successful and help identify areas that require interventions the most to mitigate socio-spatial segregation. Highlights: This return of the state in land acquisition and urban (re)development has resulted in DVRC in China. DVRC are examined to depreciate nearby housing price by 10, 440 CNY. The disamenity effects of DVRC on housing price is heterogeneous across space. Two typical areas where the proximity to DVRC appreciates housing price are identified. The trial of promoting the social integration of land-lost peasants through mixed-use developments was unsuccessful.